[4+1] Cyclizations to Enantiopure Multifunctional Cyclopentanes from d-Glucose Using Formyl Dianion Synthons - Oelze, Silke; Bräuer, Nico; Michel, Tycho; Schaumann, Ernst; Kirschning, Andreas (Synlett, 2023)
The [4+1] cyclization of a sugar-based epoxytosylate with various C1 dianion equivalents provide highly functionalized homochiral cyclopentane derivatives. For these, a follow-up chemistry was developed to provide various cyclopentane building blocks as starting points for natural product syntheses. The [4+1] domino protocol relies on a 1,4-Brook rearrangement, which is essential for generating the second carbanion.
Keywords: Brook rearrangements; cyclizations; domino reactions; ex-chiral pool synthesis; prostaglandins